2020
DOI: 10.4236/pp.2020.1111026
|View full text |Cite
|
Sign up to set email alerts
|

Household Disposal and Recycling of Medication in Saudi Arabia: A Call for Introducing Drug Take-Back Programs

Abstract: Background: Inappropriate disposal practices of medicinal products by households can harm nature. Alternatively, passing unused medications to friends and family members can have undesirable consequences as the quality of the product is in question. Objective: To investigate the disposal and recycling practices of medicinal products by households in Saudi Arabia. Methods: A cross-sectional questionnaire designed to investigate disposal and recycling practices aimed at households in Saudi Arabia. Phone intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This study showed that 28 % of the respondents were less likely to adhere to policies and guidelines which control medication waste disposal. This finding was consistent with a finding from a previous study, in which the participants pharmacists’ response that there was no clear census policy on how to appropriately dispose of medication waste ( Lucca et al, 2019 , Alqurshi, 2020 ). The Food and Drug Authority (FDA), in United States, had launched several guidelines for the safe disposal of unused and expired medicine which includes the take-back program ( Hendaus et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study showed that 28 % of the respondents were less likely to adhere to policies and guidelines which control medication waste disposal. This finding was consistent with a finding from a previous study, in which the participants pharmacists’ response that there was no clear census policy on how to appropriately dispose of medication waste ( Lucca et al, 2019 , Alqurshi, 2020 ). The Food and Drug Authority (FDA), in United States, had launched several guidelines for the safe disposal of unused and expired medicine which includes the take-back program ( Hendaus et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Patient education, improving prescribing practices, patients’ engagements with their healthcare to ensure their medication adherence, and establishing a nation-wide return and medication disposal program in the community are the four proposed approaches to overcome medication waste issue. ( Alqurshi, 2020 , Alghadeer and Al-Arifi, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The analysis of the behavior of pharmacy students in Saudi Arabia showed that the percentage of female students found to throw unused or expired drugs into the household garbage was significantly higher compared with the male students [ 37 ]. On the other hand, Akkici et al (2018), in studies conducted among respondents in Turkey, observed that a higher percentage of women declared having changed their unused drug handling practice (49.9%) than men (38.5%) [ 80 ], whereas age, gender or education did not affect the environmental behavior of the respondents in Romania, the USA, Thailand or Ireland with regard to the handling of unused drugs [ 6 , 46 , 59 , 71 , 79 ].…”
Section: Methods Of Disposal Of Unused/expired Pharmaceuticalsmentioning
confidence: 99%